The influence of single magnetic impurities on the conductance of quantum microconstrictions: Электpонные свойства металлов и сплавов - Namiranian, A.; Kolesnichenko, Yu. A.; Omelyanchouk, A. N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
The nonlinear ballistic conductance of three-dimensional quantum microconstrictions, which contain a magnetic impurities, is investigated. The nonlinear part of the conductance, which is due to the interaction of electrons with magnetic impurities, is obtained. The analytical results have been analyzed numerically. It is shown that the intensity of the Kondo anomaly in the conductance as a function of the applied voltage depends on the diameter of the constriction and the positions of the impurities.